Upaya meningkatkan prestasi dan kualitas belajar kimia dengan metode pembelajaran penemuan konsep - Sriyono Iqbal (Indonesian Journal of Educational Development, 2021)
This research is a classroom action research that aims to: 1) determine the increase in student achievement after the application of concept discovery learning and 2) determine the quality of learning after concept discovery learning is applied. The research subjects were 33 students of XII-IPA 3 SMA Negeri 1 Mejayan, Madiun Regency in the academic year 2019/2020. The research object is the learning achievement and the quality of chemistry learning. Learning achievement data were collected using learning outcomes tests, while learning quality data were collected through observations of student learning motivation. The research data were analyzed descriptively qualitatively. The results showed that learning with concept discovery had a positive impact in increasing student achievement which was marked by an increase in student learning completeness in each cycle, namely cycle I (63.63%), cycle II (78.78%), cycle III (87 , 87%). The application of the concept discovery learning method has a positive effect, namely it can increase student motivation as indicated by the average student's answer which states that students are interested and interested in the concept discovery learning method so that they become motivated to learn. Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk: 1) mengetahui peningkatan prestasi belajar siswa setelah diterapkannya pembelajaran penemuan konsep dan 2) mengetahui kualitas pembelajaran setelah diterapkan pembelajaran penemuan konsep. Subjek penelitian adalah siswa XII-IPA 3 SMA Negeri 1 Mejayan Kabupaten Madiun Tahun Pelajaran 2019/2020 yang berjumlah 33 orang. Objek penelitian adalah prestasi belajar dan kualitas pembelajaran kimia. Data prestasi belajar dikumpulkan menggunakan tes hasil belajar, sedangkan data kualitas pembelajaran dikumpulkan melalui observasi motivasi belajar siswa. Data penelitian dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pembelajaran dengan penemuan konsep memiliki dampak positif dalam meningkatkan prestasi belajar siswa yang ditandai dengan peningkatan ketuntasan belajar siswa dalam setiap siklus, yaitu siklus I (63,63%), siklus II (78,78%), siklus III (87,87%). Penerapan metode pembelajaran penemuan konsep mempunyai pengaruh positif, yaitu dapat meningkatkan motivasi belajar siswa yang ditunjukan dengan rata-rata jawaban siswa yang menyatakan bahwa siswa tertarik dan berminat dengan metode pembelajaran penemuan konsep sehingga mereka menjadi termotivasi untuk belajar.